Building Ambient Temperature Measurement using Industrial Wireless Mesh Technology - Duc Chung, T. (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper presents an approach to measure building ambient temperature using industrial wireless mesh technology (WirelessHART) based on command line interface (CLI) with wireless network manager from a laptop host. Based on the experiment with five wireless nodes (motes) in a laboratory environment, it is found that on average, the measured temperatures are close to 22Â°C. In addition, all motes have similar temperature pattern even though they are located at different places in the laboratory. When there is a change in the laboratory's environment i.e., the entry door is opened / closed, the measured temperatures at all motes increase / decrease accordingly. In addition, the mote nearest to the entry door has the highest average temperature while the mote furthest to the door has the lowest average temperature. Furthermore, the mote attached to a time-varying heat source, i.e., the laptop fan, has the highest temperature deviation. Â© 2019 IEEE.